The urban informal sector: The inconsistency of the conventional paradigm and a new approach. - De la Piedra, Enrique (1986)
Traditionally, the urban informal sector (UIS) has either not been taken into account in the design and application of economic policy or has been so erroneously, even though its presence modifies the evolution of the macroeconomic and distributive variables to a considerable extent. This fact, which arises in no small measure from the insufficiencies and inconsistencies of the conventional paradigm, explains in part in the achievement of its targets during the last years in Latin America. It is then necessary to analyze in detail the short run economic role of the UIS. When the author defines the latter as a sector of economy, on account of its peculiar economic rationality and of the existence of various and complex supply and demands mechanisms through which it relates to the rest of the economy, he lays down the foundations of a new theoretical point of view on the UIS, which, on the other hand, is intimately linked in its conception with the evolution of the relevant literature in the last fifteen years. The analysis of the design of economic policy in general to improve but also to take into consideration the situation of low income groups and to appreciate the latter's capacity to collaborate in the processes of adjustment, reactivation, and growth.​